1991
DOI: 10.1038/bjc.1991.478
|View full text |Cite
|
Sign up to set email alerts
|

Nucleolar organiser regions (AgNORs) as predictors in transitional cell bladder cancer

Abstract: Summary The predictive value of silver stained nucleolar organiser regions (AgNORs) was assessed in 229 patients with transitional cell bladder cancer followed up for over 10 years. The AgNORs were enumerated in pretreatment biopsy specimens. The AgNORs were related to clinical stage (T)(P = 0.0111), papillarity (P<0.0001), WHO grade (P<0.0001), DNA ploidy (P = 0.0010) and S-phase fraction (P<0.0001). Tumours presenting with pelvic lymph node involvement (P= 0.0085) or metastasis (P = 0.0780) at the time of di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
23
0

Year Published

1992
1992
2005
2005

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(29 citation statements)
references
References 21 publications
6
23
0
Order By: Relevance
“…The results are in full agreement with the results of Ki-67 immunolabelling in TCC (Tsujihashi et al, 1991;Bush et al, 1991). A similar relationship between papillary status, T-category, Ag-NORs (Lipponen et al, 1991d), nuclear morphometric variables (Lipponen et al, 1990b), mitotic indices (Lipponen & Eskelinen, 1990b), DNA ploidy and S phase fraction (Lipponen et al, 1991c) Ag-NOR analysis (Lipponen et al, 1991d), mitotic frequency analysis (Lipponen et al, 1990a) and Ki-67 immunolabelling (Tsujihashi et al, 1991;Bush et al, 1991).…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…The results are in full agreement with the results of Ki-67 immunolabelling in TCC (Tsujihashi et al, 1991;Bush et al, 1991). A similar relationship between papillary status, T-category, Ag-NORs (Lipponen et al, 1991d), nuclear morphometric variables (Lipponen et al, 1990b), mitotic indices (Lipponen & Eskelinen, 1990b), DNA ploidy and S phase fraction (Lipponen et al, 1991c) Ag-NOR analysis (Lipponen et al, 1991d), mitotic frequency analysis (Lipponen et al, 1990a) and Ki-67 immunolabelling (Tsujihashi et al, 1991;Bush et al, 1991).…”
Section: Discussionsupporting
confidence: 79%
“…Flow cytometry, Ag-NOR method and mitotic frequency analysis The results and method of flow cytometry (Lipponen et al, 1991c), Ag-NOR technique (Lipponen et al, 1991d) and mitotic frequency analysis (Lipponen et al, 1990a(Lipponen et al, ,b, 1991b in the present cohort has been reported previously in the literature. The reader is referred to original reports for details.…”
Section: Histological Methodsmentioning
confidence: 87%
See 1 more Smart Citation
“…Methods that have been used to measure cell proliferation, so far, include flow cytometry [20, 22], mitotic indices [24], Ki-67 immunostaining, bromodeoxyuridine incorporation [25], proliferating cell nuclear antigen expression and nucleolar organizer regions [13, 26]. According to Lipponen et al [24], the M/V index appeared to be the best histological prognostic factor in SBC [24].…”
Section: Discussionmentioning
confidence: 99%
“…Moving a step further, Pich verified that AgNOR staining could be used as an effective independent prognostic factor in prospective studies. Not surprisingly, increases in AgNOR staining correlates well with other disease prognostic markers such as increased DNA content in breast cancer, [30,33,34] bladder cancer, [35] and ovarian cancer, [36] as well as markers of proliferation including BrdU staining, [37][38][39] tritiated thymidine uptake, [24] and percentage of S-phase cells. [40,41] The list of AgNOR quantified cancers is nearly exhaustive, as Pich has noted, [32] with the common theme being the invaluable definitive measure of tumor pathology provided by proper AgNOR staining and quantification.…”
Section: Agnor As a Clinical Marker For Cancermentioning
confidence: 99%